From strategy to implementation: a relational model of vertical-horizontal alignment in Indonesian financial services - Andy Iskandar Iskandar; Elliot simangungsong; Eka Ardianto (Manajemen dan Bisnis, 2026)
Vertical-horizontal strategy alignment is essential for translating top management's formulated strategy into coherent work priorities across hierarchical levels and organizational functions. However, limited research has explicitly examined the enabling factors of vertical-horizontal alignment and the relational mechanism through which these factors shape strategy implementation. This study aims to identify the key factors enabling vertical-horizontal alignment and to develop a relational model explaining how these factors jointly support strategy implementation. Adopting an interpretive qualitative approach and a multiple-case study design, the study draws on 20 semi-structured interviews with directors, general managers, and managers from four Indonesian financial services organizations. The findings reveal six core enablers: clear strategy, strong leader, strategic management office, management system, communication, and open discussion. These enablers do not operate in isolation but interact as a dynamic relational system in which clear strategy functions as the central integrative factor linking strategy formulation and implementation, while the entry point into the alignment process may vary across organizations. This study contributes to the strategy implementation literature by reframing vertical-horizontal alignment as a dynamic relational process. Practically, it provides a diagnostic basis for organizations seeking to strengthen cross-level and cross-functional alignment in strategy implementation.